THIN LAYER CHROMATOGRAPHY AND HIGH PRESSURE LIQUID CHROMATOGRAPHY PROFILING OF PLANT EXTRACTS OF VIOLA ODORATA LINN - SANDHYA MITTAL, (International Journal of Pharma and Bio Sciences, 2013)
Medicinal plant contains matter that can be used for therapeutic reason or which are precursors for the production of useful drugs. Very few and periodic works are there in the literature regarding the phytochemistry and TLC of Viola odorata L. TLC profiling of plant extract gives an idea about the presence of various phytochemicals. Different Rf (Retention factor) value of various phytochemicals provide valuable clue regarding their polarity and selection of solvents for separation of phytochemicals. HPLC profile of petroleum ether extract of Viola odorata have characteristics peaks at retention time 2.885, 3.370, 3.487, 3.900, 4.067, 4.191, 5.207, 6.724 (Stigmasterol), 17.698 (Lupeol), 18.174 (β-Sitosterol), 23.118. These peaks showed that there are different compounds and characteristic fingerprints for each drug to judge in an herbal formulation.